EDUCATIONAL SYSTEM OF THE XXI CENTURY AS AN ESCAPE FROM NAKED SIGNS OF VACUOUSNESS - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The philosophical analysis of education of man at the beginning of the XXI century is represented. The special attention is drawn to essential changes in the national system of education.